Evolução do Batólito Itaporé e rochas encaixantes, Orógeno Araçuaí (MG): geoquímica, geocronologia e petrogênese - Carolina Deluca de Moura (2018)
The Araçuaí orogen (SE Brazil) records a long period of magmatic activity from the earliest pre-collisional (ca. 630 Ma) to the latest post-collisional (ca. 480 Ma) intrusions. The Itaporé batholith, located in the Coronel Murta - Itinga region (southeast Brazil), includes a number of granitic bodies that has been ascribed to the post-collisional G4 supersuite (ca. 530-500 Ma). According to field and analytical data, this batholith has been subdivided into three main granitic facies: i) biotite granite (Qtz + Kfs + Pl+ Bt + Ap + Zrn ± Ms ± Mnz ± Ttn ± Aln), ii) two-mica leucogranite (Qtz + Kfs + Pl + Ms + Bt ± Grt + Zrn + Mnz + Ap ± Tur), and iii) pegmatoid granite (Kfs + Qz + Pl + Ms ± Bt ± Ap ± Tur ± Grt ± Brl). The western part of the batholith is dominated by biotite monzogranite while the eastern part consists of leucogranites (syenogranites to monzogranites) locally presenting gradational contacts with pegmatoid granite. U-Pb (ICP-MS) ages obtained from apatite, monazite and zircon reveal a long and complex evolution history from 540 Ma to 474 Ma, encompassing magmatic crystallization, deuteric activity and thermal metamorphism. Dating on zircon yielded emplacement ages around 538 Ma for biotite granites. Geochemical signatures suggest two different petrogenetic processes and magma sources for the biotite and two-mica granites. On the other hand, similar evidence provided by petrographic, mineral chemistry and U-Pb monazite investigations reveal a common stage of fluid interaction between 522 Ma and 527 Ma, which are associated with volatile-rich fluids scape during deuteric alteration of the two-mica leucogranites. The fluid evolution after magma solidification promoted element mobility under subsolidus conditions and postpone its thermal lifetime. Finally, the youngest evolution period (508 - 474 Ma) marked by monazite, apatite and zircon ages from both biotite and two-mica granites can be related to the final stabilization of the Araçuaí orogen, during the late post-collisional stage, involving fluid percolation probably related to crustal thinning and asthenospheric upwelling. Still focusing on the geodynamic evolution of the Araçuaí orogen, another object of this study are the country rocks of the Itaporé batholith that include graywackes, pelites and orthoconglomerates of the Salinas Formation, metamorphosed on the greenschist (biotite zone) to amphibolite facies (sillimanite zone). Based on lithochemical signatures we made approaches about the source areas and geotectonic settings that possibly contributed to fill the Salinas basin. The lithochemistry suggest limited chemical weathering on the sediment sources and deposition relatively close to the provenance areas. The samples show good correlations between the lithochemical and mineralogical compositions, in respect to the variable amounts of metamorphic minerals typical of pelitic (micas, garnet and other peraluminous silicates) and psammitic (feldspars, quartz) fractions. The provenance of sedimentary protoliths are clearly related to continental magmatic arc and active continental margin environments, suggesting a main provenance from the Rio Doce magmatic arc.